The cost of research: Lasting effects of capture, surgery and muscle biopsy on brown bear (Ursus arctos) movement and physiology - Alexandra Thiel; Anne G Hertel; Sylvain Giroud; Andrea Friebe; Boris Fuchs; Jonas Kindberg; Anne Randi Græsli; Jon M Arnemo; Alina L Evans (Animal Welfare, 2023)
Animal models are a key component of translational medicine, helping transfer scientific findings into practical applications for human health. A fundamental principle of research ethics involves weighing the benefits of the research to society against the burden imposed on the animals used for scientific purposes. The utilisation of wild animals for research requires evaluation of the effects of capture and invasive sampling. Determining the severity and duration of these interventions on the animal’s physiology and behaviour allows for refining study methodology and for excluding or accounting for biased data. In this study, 39 Scandinavian brown bears (Ursus arctos) captured either while hibernating in winter or via helicopter in summer and that underwent surgery as part of a human health project had their movement, body temperature and timing of onset of hibernation compared with those of 14 control bears that had not been captured during the same period. Bears captured in winter and summer showed decreased movement from den exit until late summer, compared to those in the control group. Bears captured in summer showed reduced movement and body temperature for at least, respectively, 14 and 3 days, with an 11% decrease in hourly distance, compared to pre-capture levels, but did not differ in the timing of hibernation onset. We reveal that brown bear behaviour and physiology can be altered in response to capture and surgery for days to months, post-capture. This has broad implications for the conclusions of wildlife studies that rely upon invasive sampling.